A economia das trocas simbólicas no campo do Taekwondo - Pimenta, Thiago Farias Da Fonseca [UNESP]; Drigo, Alexandre Janotta [UNESP] (FapUNIFESP (SciELO), 2015)
The present article aimed to identify how the economy of symbolic exchanges is constituted in the sport field of Taekwondo. We analyzed five semi-structured interviews of the masters of this martial art, agents in the State of São Paulo (2007), in order to identify this economy which is possibly reproduced in this field. We used the theoretical framework of Pierre Bourdieu to analyze the interviews. It was considered that these symbolic impositions are reproduced and resignified, and they serve as a tool for maintaining both power and positions within the sports field of Taekwondo.
The symbolic trade economy in Taekwondo field
Keywords: Martial arts; Sports field; Symbolic exchanges; Taekwondo